DOI: 10.26686/wgtn.17058068
|View full text |Cite
|
Sign up to set email alerts
|

An Archaeomagnetic Study of Hangi Stones in New Zealand

Abstract: <p>Burnt or fired archaeological artefacts often retain a record of the magnetic field in which they were last heated and cooled. Over the past four years we have collected oriented hangi stones from 10 archaeological sites spread across the North and South Islands of New Zealand. The stones vary in lithology from andesites, originating from the central North Island volcanoes, favoured by Maori for their durability and with remanent magnetization up to 30 A/m, to sandstones and schists from the main axia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 57 publications
(179 reference statements)
0
5
0
Order By: Relevance
“…These stones, having been heated to such high temperatures and cooled, have recorded the magnetic field of the time. Under ideal conditions and meticulous fieldwork, careful analysis of the TRM may yield palaeodirections and palaeointensities of the geomagnetic field at the time (Kinger, 2017). Experimentally, it was successfully demonstrated that the hāngī stones retain the TRM record of the time the hāngī was last used.…”
Section: Archaeomagnetismmentioning
confidence: 99%
See 4 more Smart Citations
“…These stones, having been heated to such high temperatures and cooled, have recorded the magnetic field of the time. Under ideal conditions and meticulous fieldwork, careful analysis of the TRM may yield palaeodirections and palaeointensities of the geomagnetic field at the time (Kinger, 2017). Experimentally, it was successfully demonstrated that the hāngī stones retain the TRM record of the time the hāngī was last used.…”
Section: Archaeomagnetismmentioning
confidence: 99%
“…Hāngī stones that are heated above the Curie temperature of their constituent magnetic minerals and subsequently cooled, acquire a thermoremanent magnetization (TRM) which is parallel to the ambient field at the time. This event will erase any previous remanent magnetization (RM) and hence, can be termed as characteristic remanent magnetization (ChRM) or hāngī remanent magnetization (HRM) (Kinger, 2017) of the hāngī stone. The intensity of this magnetization is proportional to the strength of the ambient field.…”
Section: Nrm Measurementmentioning
confidence: 99%
See 3 more Smart Citations